Equity, empowerment and gender relations: A literature review of special relevance for climate-smart agriculture programming - Villavicencio, Francia; Rosimo, Magnolia M.; Vidallo, Rene R.; Monville-Oro, Emilita; Gonsalves, Julian Francis (2018)
The brief summarizes the results of a literature review on equity, empowerment and gender relations for climate-smart agriculture programming. The review found out that a wider and more equitable gender sensitivity is now seen amongst policy makers and local government, with a corresponding enhanced and out-scaled uptake on CSA. Improved access to resources, information, markets and decision-making opportunities of women will bring them on par with men as equal partners in climate change and disaster risk reduction efforts. Applying social learning improved the adaptive capacities of women.